The Development of Tuberculosis Treatment Room in Humid Tropical Climate - Wisdom Sandjaya Papendang; Samuel Yudhatama (Journal of Artificial Intelligence in Architecture, 2022)
Developing countries with a humid tropical climate, such as Indonesia, still have a severe problem with Tuberculosis (TB). Mycobacterium tuberculosis (MTB) mainly causes TB and is transmitted through droplets released by active TB patients into the air that progress faster in humid tropical climates. Health workers are at high risk of contracting TB bacteria from TB patients because nosocomial infections (healthcare-associated infections) categorize as TB. Public Health Centers usually provide generic rooms but are not explicitly designed to minimize TB infections. The Indonesian government does not offer a TB treatment room design, so this research developed a Tuberculosis Treatment Room (TBTR) prototype using a computational fluid dynamics simulation. The TBTR prototype was split into medicine and sputum room. The simulation showed that the TBTR's air change per hour was between 77 and 94, far above the minimum standard of 12. In addition, TBTR showed indoor air 80cm above the floor flowed upward and out through the ceilings, while indoor air below 40cm above the floor flowed through lower openings. Those ventilation mechanisms expelled the indoor bacteria out and minimized infection